Release of airborne particles and Ag and Zn compounds from nanotechnology-enabled consumer sprays: Implications for inhalation exposure. (April 2017) - Calderón, Leonardo; Han, Taewon T.; McGilvery, Catriona M.; Yang, Letao; Subramaniam, Prasad; Lee, Ki-Bum; Schwander, Stephan; Tetley, Teresa D.; Georgopoulos, Panos G.; Ryan, Mary; Porter, Alexandra E.; Smith, Rachel; et al.
Abstract: The increasing prevalence and use of nanotechnology-enabled consumer products have increased potential consumer exposures to nanoparticles; however, there is still a lack of data characterizing such consumer exposure. The research reported here investigated near-field airborne exposures due to the use of 13 silver (Ag)-based and 5 zinc (Zn)-based consumer sprays. The products were sprayed into a specially designed glove box, and all products were applied with equal spraying duration and frequency. Size distribution and concentration of the released particles were assessed using a Scanning Mobility Particle Sizer and an Aerodynamic Particle Sizer. Inductively coupled plasma mass spectrometry (ICP-MS) was used to investigate the presence of metals in all investigated products. Spray liquids and airborne particles from select products were examined using transmission electron microscopy (TEM) and Energy Dispersive X-ray Spectroscopy (EDS). We found that all sprays produced airborne particles ranging in size from nano-sized particles (<100 nm) to coarse particles (>2.5 μm); however, there was a substantial variation in the released particle concentration depending on a product. The total aerosol mass concentration was dominated by the presence of coarse particles, and it ranged from ∼30 μg/m 3 to ∼30, 000 μg/m 3 . The TEM verified the presence of nanoparticles and their agglomerates in liquid and airborne states. The products were found to contain not only Ag and Zn compounds - as advertised on the product labeling - but also a variety of other metals including lithium, strontium, barium, lead, manganese and others. The results presented here can be used as input to model population exposures as well as form a basis for human health effects studies due to the use nanotechnology-enabled products. Highlights: Eighteen consumer sprays with Ag and Zn nanoparticles analyzed for possible exposure. All sprays produced nanoscale (<100 nm) and coarse aerosol particles (>2.5 μm). Presence of silver, zinc and various other metals determined in sprays and aerosol. Presence of nanoparticle and agglomerates in liquid and airborne state confirmed.